Green building certification systems : assessing sustainability : international system comparison : economic impact of certifications - Ebert, Thino, ....-; Essig, Natalie, ....-; Hauser, Gerd, ....- (München : Institut für internationale Architektur-Dokumentation, 2011)
Certification systems for buildings, such as BREEAM, LEED or DGNB, aim to make sustainability in architecture transparent and provide a means of comparison. At the same time, the systems are subject to dynamic development, and it is very apparent that the individual systems are in competition with one another. This book provides insight into the many facets of green labels. The most important certificates with their system variants and assessment methods are introduced in detail, and information on the certification processes and costs is provided. Selected buildings are used to illustrate the core themes, the certification processes and the differences between the various labels. "Green Building Certification Systems" is therefore an important reference book for architects and planners, clients and project managers, as well as manufacturers and construction companies. International framework conditions for sustainable building Certification systems in detail: BREEAM, LEED, DGNB, MINERGIE, HQE, EU GreenBuilding Programme, CASBEE Planning processes and documentation requirements Certification costs Project examples Market potential for green building certificates
Keywords: Architectuur; Duurzaam bouwen; Ecologisch bouwen; Kwaliteitssystemen; Sustainable buildings